Phylogenetic position of gastrostomobdellid leeches (Hirudinida, Arhynchobdellida, Erpobdelliformes) and a new family for the genus Orobdella - Nakano, Takafumi; Zainudin, Ramlah; Hikida, Tsutomu (The Norwegian Academy of Science and Letters, 2011)
The leech family Gastrostomobdellidae is characterized by its possession of an agnathous and euthylaematous pharynx, a ventral gastropore and a gastroporal duct. In this study, the phylogenetic position of two gastrostomobdellid genera, Gastrostomobdella and Orobdella, was investigated using partial nucleic 18S, 28S rDNA and mitochondrial 12S rDNA sequences. Our phylogenetic analyses showed that both Gastrostomobdella and Orobdella are nested within Erpobdelliformes, but Gastrostomobdellidae is not a monophyletic taxon. Orobdella is a sister taxon of the other Erpobdelliformes taxa. The phylogenetic position of Gastrostomobdella within the clade of Gastrostomobdella, Erpobdellidae and Salifidae still remains uncertain. According to the reconstruction of the ancestral state of the pharynx in Erpobdelliformes, a euthylaematous pharynx is considered to be plesiomorphic in this taxon. Examination of Gastrostomobdella and Orobdella specimens indicates that the morphology of the gastroporal duct of Orobdella is quite different from that of Gastrostomobdella. A new family, Orobdellidae fam. nov., was therefore erected for the genus Orobdella. Orobdellidae is characterized by its possession of a generally tubular gastroporal duct, lying on the female organ